1984
DOI: 10.1063/1.447005
|View full text |Cite
|
Sign up to set email alerts
|

Electric-dipole moment of CaF (X 2Σ+) by molecular beam, laser-rf, double-resonance study of Stark splittings

Abstract: Articles you may be interested inLaserrf double resonance spectroscopy of 174YbF in the X 2Σ+ state: Spinrotation, hyperfine interactions, and the electric dipole moment Erratum: Hyperfine structure of the X 2Σ+ ground state of Ca3 5Cl and Ca3 7Cl by molecularbeam, laserrf double resonance [ J. Chem. Phys. 7 6, 3993 (1982)] J. Chem. Phys. 80, 2246 (1984); 10.1063/1.447300 Hyperfine structure of the X 2Σ+ ground state of Ca35Cl and Ca37Cl by molecularbeam, laserrf double resonance

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

1984
1984
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(25 citation statements)
references
References 21 publications
0
24
1
Order By: Relevance
“…8,9 An effective value of ␣ ϩ ϭ7.6 Å 3 , which is significantly less than the theoretical free ion value of ␣ ϩ ϭ12 Å 3 , was required to fit the ground state dipole moments of other calcium monovalent diatomic compounds 18 and was used here. Ligand field calculations 17 showed that s, p and d Ca ϩ orbital mixing is virtually the same for all calcium monohalides justifying the adaptation of the same value.…”
Section: ͑2͒mentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 An effective value of ␣ ϩ ϭ7.6 Å 3 , which is significantly less than the theoretical free ion value of ␣ ϩ ϭ12 Å 3 , was required to fit the ground state dipole moments of other calcium monovalent diatomic compounds 18 and was used here. Ligand field calculations 17 showed that s, p and d Ca ϩ orbital mixing is virtually the same for all calcium monohalides justifying the adaptation of the same value.…”
Section: ͑2͒mentioning
confidence: 99%
“…Over the past ten years the measurement of dipole moments of a variety of monovalent calcium compounds has been performed. [8][9][10][11][12][13][14] Monovalent calcium compounds are ideal candidates for such a study because they are relatively easy to create and have intense, unperturbed, optical spectra. By interpreting the determined values of a description of their ionic bonding nature has evolved and subsequently semiempirical electrostatic polarizability, 15,16 ligand field, 17 and ab initio 18 models that quantitatively predict dipole moments have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Controlled microwave-induced dipoles are important for simulating spin Hamiltonians [7,10,47,48], studying topological superfluids [49], and enhancing evaporative cooling [50]. For induced dipoles of μ e = ffiffi ffi 3 p , where μ e ¼ 3.07 D is the dipole moment of CaF [51], and taking a realistic spacing of 0.5 μm, the dipole-dipole interaction energy is a few kHz, comparable to the resolution we achieve. Thus, our work demonstrates many of the key capabilities needed for the applications of laser-cooled molecules.…”
mentioning
confidence: 76%
“…The determined μ e values for BaF are compared with values for isovalent CaF [33,34] and SrF [35,36] in Table V. Only the μ e values for the A 2 3/2 (υ = 0) spin-orbit state were measured for CaF and SrF.…”
Section: Discussionmentioning
confidence: 99%